Analysis of Student Errors in Solving Trigonometry Problems - Ully Hidayati (JME (Journal of Mathematics Education), 2020)
This study aims to obtain a picture of student errors in working tests on Trigonometry. This research was conducted with a qualitative approach and was descriptive. The subjects studied were Mathematics Education students in the third semester of Class A of the University of Sembilanbelas November Kolaka in the Academic Year 2019/2020. This study uses an instrument in the form of a Final Examination in Trigonometry courses. Based on the research results obtained, an illustration that students' mistakes in working on problems in the Trigonometry course are caused by students not understanding the questions, the lack of accuracy in basic mathematical operations, and mastery of the concepts of trigonometry that students have.